OPINI KELUARGA TENTANG FAKTOR-FAKTOR YANG MENYEBABKAN TERJADINYA GANGGUAN JIWA PADA ORANG DENGAN GANGGUAN JIWA (ODGJ) - Seri, Seri Seri (Jurnal Kesehatan Ilmiah Aufa Royhan, 2022)
Introduction: The prevalence of mental disorders continues to increase every year caused by somatic factors, psychosocial factors and socio-cultural factors. This study aims to determine family opinions about the factors that cause mental disorders in people with mental disorders. Methods: This type of research is quantitative using a descriptive research design and a cross sectional approach. The sample is the family of people with mental disorders (ODGJ) as many as 65 respondents. The sampling technique was purposive sampling. Questionnaire research instrument.. The analysis used univariate analysis. Results: The results showed that family opinions about the factors that cause mental disorders in people with mental disorders are the most dominant, namely genetics/heredity as much as 69.2%, disappointment and painful experiences 67.7%, stress 66.2%, socioeconomic 60%, family relationship 56.9% and drug use 53.8%. While the non-dominant factors causing mental disorders are parenting factors 24.6%, domicile 16.9%, discriminated12.3% and childhood trauma 9.2%. Conclusion: The most dominant factor causing mental disorders in ODGJ is genetics/heredity. Suggestion: Based on the results of this study, it is recommended that the public pay more attention to their mental health and avoid factors that can trigger the occurrence of mental disorders and if those who already have a risk to be more alert to avoid the occurrence of mental disorders by consulting health workers. Keywords : Factors Causing Mental Disorders, Family